"Well Built, But Poorly Roofed": Notes on The Remains of Architectural History. Issue 2 (4th May 2018) - Hyde, Timothy
Abstract : This article proposes a new perspective on the contemporary standing of architectural history by examining the transition from architectural histories grounded in and upon textuality to an architectural historical approach formulated though the theoretical understanding of cultural techniques. Taking as a case study the cabin built by the philosopher Henry David Thoreau—and posing the wilfully deceptive question "Can there be an architectural history of Walden?"—the article concludes that the transformative implication is an architectural history that is not a discipline in and of itself, but that is instead the remainder of limits defined in the techniques of other disciplines.